THU0341 Low vitamin d is associated with thrombosis in systemic lupus erythematosus. (12th June 2018) - Petri, M.; Fu, W.; Goldman, D.W.
Abstract : Background: Low vitamin D is common in systemic lupus erythematosus (SLE). It is also found in antiphospholipid syndrome. Vitamin D has effects on tissue factor, PAI-1, thrombomodulin and platelet aggregation that suggest it has an anti-thrombotic role. We asked whether low vitamin D was associated with thrombosis in SLE, adjusting for lupus anticoagulant. Objectives: We asked whether low vitamin D was associated with thrombosis in SLE, adjusting for lupus anticoagulant. Methods: A total of 1, 392 SLE patients were included in the analysis. At the first visit when vitamin D was measured, 76.7% had levels of 25-hydroxyvitamin D<40 ng/mL. The SLE patients were: 92% female, mean age 42.9 years, and ethnicity 50% Caucasian, 41% African American. 27% patients had a history of thrombosis; 7% stroke, 4% MI and 14% DVT. Results: Vitamin D, measured either as a continuous variable or as "low" (<40 ng/mL) vs. normal, was associated with any thrombosis and with DVT. Conclusions: Low vitamin D was significantly associated with any thrombosis and with DVT (even after adjustment for lupus anticoagulant). In prospective models it remained significantly associated with any thrombosis. As supplementation with vitamin D was proven to reduce thrombosis in an oncology randomised clinical trial, vitamin D replacement should become routine in SLE patients at risk for thrombosis. Disclosure of Interest: None declared